2020
DOI: 10.1186/s13071-020-04321-w
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus sphaericus exposure reduced vector competence of Anopheles dirus to Plasmodium yoelii by upregulating the Imd signaling pathway

Abstract: Background: Vector control with Bacillus sphaericus (Bs) is an effective way to block the transmission of malaria. However, in practical application of Bs agents, a sublethal dose effect was often caused by insufficient dosing, and it is little known whether the Bs exposure would affect the surviving mosquitoes' vector capacity to malaria. Methods: A sublethal dose of the Bs 2362 strain was administrated to the early fourth-instar larvae of Anopheles dirus to simulate shortage use of Bs in field circumstance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The microbiota can play a major role in the antiviral response of mosquitoes, either by secreting antiviral or proviral molecules or by modulating the immunity response [ 401 , 402 , 403 , 404 ]. Some studies have shown alterations in the susceptibility to arbovirus or protozoa in mosquitoes exposed to sublethal doses of L. sphaericus or Bti [ 404 , 405 , 406 , 407 ]. Therefore, a broader analysis of the potential impact of L. sphaericus and Bti on mosquito biology is required to assess the consequences of their use beyond the issue of resistance onset.…”
Section: Impact On Life Traitsmentioning
confidence: 99%
“…The microbiota can play a major role in the antiviral response of mosquitoes, either by secreting antiviral or proviral molecules or by modulating the immunity response [ 401 , 402 , 403 , 404 ]. Some studies have shown alterations in the susceptibility to arbovirus or protozoa in mosquitoes exposed to sublethal doses of L. sphaericus or Bti [ 404 , 405 , 406 , 407 ]. Therefore, a broader analysis of the potential impact of L. sphaericus and Bti on mosquito biology is required to assess the consequences of their use beyond the issue of resistance onset.…”
Section: Impact On Life Traitsmentioning
confidence: 99%
“…stephensi Hor strain was maintained at 28 °C and 70–80% relative humidity with a 12-h light/dark photocycle, according to the standard rearing procedures in the laboratory. The adults and larvae were fed on 10% sugar solution and a powdered mix of dry degreased pork liver and yeast at a ratio of 1:4, respectively [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is due to the differentiation in cell wall structure between Gram-positive and Gram-negative bacteria. A relatively large set of bacteria can be used for this purpose, such as Bacillus pasteurii [31], Bacillus sphaericus [32], Escherichia coli [33], Bacillus subtilus [34], Bacillus cohnii [35], Bacillus pseudofirmus [36], and Bacillus halodurans [27]. In this paper, however, we will limit our selection for the sake of clarity.…”
Section: General About Organismsmentioning
confidence: 99%